The Occupational/Career Decision-Making Processes of Intellectually Gifted Adolescents From Economically Disadvantaged Backgrounds: A Mixed Methods Perspective. (January 2019) - Jung, Jae Yup; Young, Marie
This mixed methods study investigated the occupational/career decision-making processes of intellectually gifted adolescents from economically disadvantaged backgrounds. In the first phase, interview data from 26 Australian adolescents, who were simultaneously intellectually gifted and of low socioeconomic status background, were analyzed using grounded theory to develop four models of occupational/career decision-making processes. In the second phase, a model that incorporated all of the constructs and relationships identified in each of the four models developed in the first phase of the study was tested and refined using structural equation modeling procedures on survey data collected from 917 economically disadvantaged intellectually gifted Australian adolescents. The resulting qualitatively developed and quantitatively refined model allowed for a clearer and a more complete understanding of the occupational/career decision-making processes of intellectually gifted adolescents from economically disadvantaged backgrounds.